REFORMS IN THE CULTURAL FIELD - AS THE BASIS OF A NEW SPIRITUAL SPACE (American Journal of Research in Humanities and Social Sciences, 2024)
This article presents opinions on the interrelationship of culture and spirituality, the importance of cultural reforms in creating a new spiritual environment. The main aspects of the reforms implemented in our country regarding the creation of a new spiritual space have been analyzed.